2017
DOI: 10.1016/j.parkreldis.2017.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Low adherence to antidepressants is associated with increased mortality in Parkinson disease patients

Abstract: Our findings suggest that poor adherence to AD is associated with increased all-cause mortality in people with PD. Given the high prevalence of depression and AD effectiveness, efforts to promote adherence should be prioritized in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
(28 reference statements)
3
15
0
1
Order By: Relevance
“…Similarly to our previous reports on mortality in other AD‐using populations (Krivoy et al, ; Krivoy et al, ; Krivoy et al, ; Shoval et al, ), our unadjusted analyses in the present study showed an increased rate of death in the higher adherence levels. As previously discussed broadly in these publications, we attribute this finding mainly to a more drug adherent behavior in the older and highly comorbid patients, therefore such findings demonstrate the importance of having the capability to adjust for important confounders.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similarly to our previous reports on mortality in other AD‐using populations (Krivoy et al, ; Krivoy et al, ; Krivoy et al, ; Shoval et al, ), our unadjusted analyses in the present study showed an increased rate of death in the higher adherence levels. As previously discussed broadly in these publications, we attribute this finding mainly to a more drug adherent behavior in the older and highly comorbid patients, therefore such findings demonstrate the importance of having the capability to adjust for important confounders.…”
Section: Discussionsupporting
confidence: 92%
“…This relationship is systematically repeated in all subtypes of cancer we studied, except for melanoma. Similarly to our previous studies in the general population and in certain other major physical disorders (Krivoy et al, ; Krivoy et al, ; Krivoy et al, ; Shoval et al, ), the beneficial effect of adherence to AD may be at least equally important in the high‐risk population of patients with cancer. Psychiatrists, Oncologists, and primary‐care physicians should step up their efforts to sustain and enhance their patients' adherence to AD, as it may be associated with increased life expectancy.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, we cannot explain the effects by direct pharmacological action. In previous research, it was reported that good adherence is associated with a decreased mortality [37, 38], while other studies report that poor adherence is associated with an increased mortality risk ([39]. However, in our study, data regarding persistence and reasons or causes of stopping the antidepressants or benzodiazepines were not available.…”
Section: Discussionmentioning
confidence: 72%